Procedencia sedimentaria de la Formación Villavicencio (Devónico inferior) en el sur de la precordillera, Mendoza, Argentina: Nuevos datos sedimentológicos y geocronológicos - Cingolani, Carlos Alberto (2013)
The Lower Devonian siliciclastic Villavicencio Formation crops out in the Mendoza Province, Argentina. The best outcrops are located to the East of Uspallata-Caracoles de Villavicencio. It is composed by massive dark grey sandstones alternating with laminated mud beds, and laminated sandy heterolithic facies showing wave action. Facies are typical of marine shallow shelf sands. Plant debris is aligned over bedding planes suggesting short transport and deposition in a low energy environment. Several levels with endemic land plant fossils (Rhyniophytoids) and palynological data (spores) provide an early Devonian age. Sandstone petrography shows mixing of recycled orogen and continental block provenances for these feldspathic-lithic wackes. Paleocurrent data has dispersion with E-W and NW-SE bidirectional trends. U-Pb ages (LA-ICP-MS) on detrital zircons show a Mesoproterozoic dominant peak suggesting mainly sources of ‘Grenville-age’ (more than 50% of the analyzed zircons) probably located to the east of the study area.